ANALISIS ORBIT SATELIT GSO - Abd. Rachman; - Neflia (Jurnal Sains Dirgantara, 2007)
Analysis of GSO satellite has done by using data from 57 satellite. It contains analysis on distortion of satellite's orbit due to perturbation forces and analysis on the station keeping maneuvers which have been done to keep the orbit on its ideal condition. Result of the analysis shows that it is not always a satellite located near the stable points (76˚E dan 252.4˚E) will oscillate about that longitudes. Ten among the post-operational satellite do oscillate about the stable points but the rest of them drift their longitudes from 0 to 360˚. The analysis also shows that orbital prediction using SDP4 model con only be accurate for prediction of inclination. Prediction of longitude, semimajor axis, and period based on TLE data are very sensitive to the related TLE.